Robert Radcliffe’s Translation of Joannes Ravisius Textor’s Dialogi (1530) and the Henrician Reformation - Juhász-Ormsby, Ágnes (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
Joannes Ravisius Textor’s Dialogi aliquot festivissimi (1530) exerted considerable influence in England in the 1530s. The English Textor movement was spurred primarily by the dialogues’ effectiveness in advancing and popularizing specific religious changes promoted by the government as part of the unfolding Henrician Reformation. Around 1540, the master of Jesus College School in Cambridge, Robert Radcliffe, dedicated a collection of prose translations of Textor’s three dialogues—A Governor, or of the Church (Ecclesia), The Poor Man and Fortune (Pauper et fortuna), and Death and the Goer by the Way (Mors et viator)—to Henry VIII. Radcliffe’s translations, especially the politically charged A Governor, demonstrate that not only his strategically selected source texts but also his method of translation helped him position himself in influential court circles and shape his image as a humanist scholar, schoolmaster, and translator.